Ultraviolet absorber chelate, coating and coated glass
By applying a double absorption peak ultraviolet absorber chelate on a single piece of glass, the problem of difficult to isolate UVA and UVB ultraviolet rays in the prior art is solved, and efficient ultraviolet isolation effect is achieved, and good weather resistance is also achieved. and wear resistance.
Patent Information
- Application Number
- CN202411516487.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively isolate UVA and UVB ultraviolet rays on single-piece glass, and the traditional ultraviolet isolation method in the form of laminated glass cannot be applied to single-piece glass.
Using an ultraviolet absorber chelate, the ultraviolet absorbers A and B are combined with the light stabilizer and catalyst to form a chelate with dual absorption peaks, which improves the coating's absorption capacity of ultraviolet light in the range of 280-400nm. .
The UV transmittance to UVA and UVB is achieved by less than 2%, improving the UV isolation capability of the coating, and maintaining good weather resistance and wear resistance.
Smart Images

Figure CN119462727A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass manufacturing, and in particular to an ultraviolet absorber chelate, a coating and a coated glass. Background Art
[0002] Functional coatings can be formed on the surface of the substrate through surface coating technology. As the requirements of different automobile OEMs for optical indicators change, the light incident angle is required to be 0°-90° relative to the glass surface, and the transmittance of UVB (280nm-315nm) and UVA (315nm-400nm) is less than 2%, which has become one of the goals to be pursued. There are new requirements for the selection and addition of optical materials in the coating. In order to be used on automobile glass, the coating must also have functions such as wear resistance and weather resistance, and the adhesion of the coating to the glass must also meet the requirements.
[0003] In order to improve the optical properties of the coating, the invention application CN103613280A (application number 201310597206) discloses a coating liquid and a UV absorbing glass for forming a UV absorbing coating. The application discloses a coating liquid for forming a UV absorbing coating on the surface of glass and other articles, a UV absorbing glass provided with a UV absorbing coating formed by the coating liquid, and a method for preparing the UV absorbing glass. The coating liquid, UV absorbing glass and method for forming the UV absorbing glass used in the application store and release electrons excited by UV rays in the UV absorber, thereby reducing the excited electrons gradually accumulated by the UV absorber in the process of absorbing UV rays, thereby protecting the UV absorber and the silica matrix, preventing the UV absorbing glass from discoloring or devitrification, and ensuring the weather resistance of the UV absorbing coating and the color consistency of the UV absorbing glass. The calculation method is based on the Tuv calculated according to the ISO9050-2003 (E) standard. Although this application can achieve Tuv (300-380nm) < 1%, Tuv (300-400nm) > 1%, which cannot meet the test requirements of UVB (280nm-315nm) and UVA (315nm-400nm) < 1%. Patent CN219446360U discloses a UV-proof high-strength laminated glass including an outer pressure-resistant glass layer, a first EVA film layer is provided at the bottom of the outer pressure-resistant glass layer, an UV-proof glass layer is pasted on the end of the first EVA film layer away from the outer pressure-resistant glass layer, an SGP intermediate film layer is provided at the bottom of the UV-proof glass layer, a high-temperature-resistant glass layer is pasted on the end of the SGP intermediate film layer away from the UV-proof glass layer, a second EVA film layer is provided at the bottom of the high-temperature-resistant glass layer, an inner sound-insulating glass layer is pasted on the end of the second EVA film layer away from the high-temperature-resistant glass layer, a laminated glass layer is provided at the center position inside the outer pressure-resistant glass layer, and a tempered glass layer is provided on the top of the laminated glass layer. However, the application of the laminated glass involved in this patent, that is, the function of blocking UV rays can only be achieved in the form of laminated glass, and cannot be applied to single-piece glass.
[0004] Therefore, it is necessary to provide a coating liquid and related products that can block both UVA and UVB ultraviolet rays. Summary of the invention
[0005] In order to solve the above problems, the purpose of the present invention is to provide a UV absorber chelate, a coating and a coated glass. The coating formed by the coating has a transmittance of less than 2% for UVA and UVB, and has a high UV isolation ability.
[0006] In order to achieve the above object, the present invention provides a UV absorber chelate, wherein the raw materials of the UV absorber chelate include, by weight:
[0007] First solvent: 10 parts to 30 parts, UV absorber A: 2.5 parts to 10 parts, UV absorber B: 2.5 parts to 15 parts, light stabilizer: 0.05 parts to 1.5 parts, coupling agent: 40 parts to 65 parts, first catalyst: 0.01 parts to 0.1 parts;
[0008] The absorption peak of the ultraviolet absorber A is located at 280nm-315nm; the absorption peak of the ultraviolet absorber B is located at 315nm-380nm.
[0009] In some specific embodiments, the ultraviolet absorber A and the ultraviolet absorber B may respectively include one or a combination of two or more of the following agents: benzophenone ultraviolet absorbers, benzimidazole ultraviolet absorbers, triazine ultraviolet absorbers, oxalic acid anilide ultraviolet absorbers, Chiguard P, Chiguard 1033, Chiguard 5540.
[0010] In some specific embodiments, when the ultraviolet absorber A and the ultraviolet absorber B are selected from one or a combination of two or more of benzophenone ultraviolet absorbers, benzimidazole ultraviolet absorbers, triazine ultraviolet absorbers, and oxalic acid anilide ultraviolet absorbers, the ultraviolet absorber A and the ultraviolet absorber B can be respectively selected from one or a combination of two or more of the same category or different categories of benzophenone ultraviolet absorbers, benzimidazole ultraviolet absorbers, triazine ultraviolet absorbers, and oxalic acid anilide ultraviolet absorbers.
[0011] In some specific embodiments, the ultraviolet absorber A and the ultraviolet absorber B can be selected from the same category of the above-mentioned ultraviolet absorbers (benzophenone ultraviolet absorbers, benzimidazole ultraviolet absorbers, triazine ultraviolet absorbers, and oxalic acid anilide ultraviolet absorbers), and the ultraviolet absorber chelate prepared in this way has a higher purity.
[0012] Specifically, the benzimidazole ultraviolet absorber can include one or a combination of two or more of 2-(2'-hydroxy-5'-methylphenyl)-benzotriazole, 2-(2'-hydroxy-3',5'-di[1,1-dimethylphenyl]phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'methylphenyl)-5-chloro-benzotriazole, Chiguard 234, and Chiguard 380.
[0013] Specifically, the benzophenone-based ultraviolet absorber may include 2-hydroxy-4-methoxybenzophenone and / or 2-hydroxy-4-octyloxybenzophenone.
[0014] Specifically, the triazine ultraviolet absorber may include one or a combination of two or more of 2-cyano-3,3-diphenylacrylate, 2-cyano-3,3-diphenylacrylate, Chiguard 1064, and Chiguard 5431;
[0015] Specifically, the oxalic acid anilide ultraviolet absorber may include N-(4-ethylbenzoate)-N',N'-(methyl,phenyl)formamidine and / or N,N'-bis(4-ethoxycarbonylphenyl)-N'-benzylformamidine.
[0016] According to a specific embodiment of the present invention, the absorption peak of the ultraviolet absorber A is generally 280-315 nm, and can further be 290-305 nm. That is, an ultraviolet absorber with an absorption peak of 280-315 nm (for example, an absorption peak of 290-305 nm) can be selected as the ultraviolet absorber A.
[0017] According to a specific embodiment of the present invention, the absorption peak of the ultraviolet absorber B is generally 315nm-380nm, and can further be 340nm-380nm. That is, an ultraviolet absorber with an absorption peak of 315nm-380nm (for example, an absorption peak of 340nm-380nm) can be selected as the ultraviolet absorber B.
[0018] According to a specific embodiment of the present invention, the UV absorber B generally has a certain type of functional group for reacting with the UV absorber A and the light stabilizer. Specifically, the functional group of the UV absorber B may include one or a combination of two or more of a hydroxyl group, a carbonyl group, and a keto group.
[0019] According to a specific embodiment of the present invention, the molecule of the light stabilizer has at least one hydroxyl group; further, the molecule of the light stabilizer may have two or more hydroxyl groups. The hydroxyl group in the light stabilizer can ensure that the light stabilizer reacts with the ultraviolet absorber A and the ultraviolet absorber B, and can make the light stabilizer have a certain solubility in water.
[0020] In some specific embodiments, the light stabilizer includes pentamethylpiperidinol, tetramethylpiperidinol, a polymer of succinic acid and (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) (also known as light stabilizer 622), polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) ester, HS-3310, One or a combination of two or more of HS-508, etc.
[0021] According to a specific embodiment of the present invention, the ultraviolet absorber A, the ultraviolet absorber B and the light stabilizer can be dissolved in water. In some specific embodiments, the solubility of the ultraviolet absorber A and the ultraviolet absorber B in 25°C water is greater than or equal to 60g / L respectively. The light stabilizer contains hydroxyl groups and also has good water solubility. Therefore, the above ultraviolet absorber chelate also has good water solubility. When the above ultraviolet absorber chelate is used to prepare a coating, it can be dissolved in the water in the coating to have good compatibility with other raw materials of the coating.
[0022] According to a specific embodiment of the present invention, the mass fraction of the ultraviolet absorber A in the raw material of the ultraviolet absorber chelate is generally 2.5 parts to 10 parts, and can be specifically 2.5 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 7.5 parts, 8 parts, 9 parts, 10 parts and the like, as well as a range with any two of the above specific values as endpoints.
[0023] According to a specific embodiment of the present invention, the mass fraction of the ultraviolet absorber B in the raw material of the ultraviolet absorber chelate is generally 2.5 parts to 15 parts, and can be specifically 2.5 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 7.5 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts and the like, as well as a range with any two of the above specific values as endpoints.
[0024] According to a specific embodiment of the present invention, the mass fraction of the light stabilizer in the raw material of the ultraviolet absorber chelate is generally 0.05 parts to 1.5 parts, and can be specifically 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 1 parts, 1.5 parts and the like, as well as a range with any two of the above specific values as endpoints.
[0025] In some specific embodiments, the ratio of the mass of the light stabilizer to the sum of the masses of the ultraviolet absorber A and the ultraviolet absorber B can be 0.02-0.3:1, specifically 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1 and other specific values, as well as ranges with any two of the above specific values as endpoints, and further can be 0.04-0.2:1.
[0026] According to a specific embodiment of the present invention, the first catalyst is capable of catalyzing the reaction between the ultraviolet absorber A, the ultraviolet absorber B and the light stabilizer.
[0027] In some specific embodiments, the first catalyst may include one or a combination of two or more of benzyltriethylammonium chloride (TEBA), tetrabutylammonium bromide (TBAB), tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.
[0028] According to a specific embodiment of the present invention, the mass fraction of the first catalyst in the raw material of the ultraviolet absorber chelate is generally 0.01 part-0.1 part, and can be specifically 0.01 part, 0.02 part, 0.03 part, 0.04 part, 0.05 part, 0.06 part, 0.07 part, 0.08 part, 0.09 part, 0.1 part and the like, as well as a range with any two of the above specific values as endpoints.
[0029] In some specific embodiments, the mass of the first catalyst can be 1 / 300-1 / 50 of the total mass of the ultraviolet absorber A and the ultraviolet absorber B, for example, it can be 1 / 300, 1 / 250, 1 / 200, 1 / 150, 1 / 100, 1 / 50 and other specific values and a range with any two of the above specific values as endpoints, and can further be 1 / 200-1 / 50.
[0030] According to a specific embodiment of the present invention, the coupling agent participates in the reaction between the ultraviolet absorber A, the ultraviolet absorber B, and the light stabilizer. The coupling agent generally contains an active group that can participate in the above reaction, such as one or a combination of two or more of an oxygen-containing hydrolyzable functional group, a hydroxyl group, an amine group, an epoxy group that can undergo a ring-opening reaction, etc.; at the same time, when the above ultraviolet absorber chelating agent is used to prepare a coating, the coupling agent also contains an active group that reacts with an alkoxysilane, and the group is not consumed in the reaction of generating the ultraviolet absorber chelate and is retained.
[0031] According to a specific embodiment of the present invention, the coupling agent may include a silane coupling agent and / or a titanate coupling agent. Specifically, the silane coupling agent may include one or a combination of two or more of γ-aminoethylaminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, and 3-(methacryloxy)propyltriethoxysilane, and the titanate coupling agent may include one or a combination of two or more of polybutyl titanate, tetra-n-propyl titanate, and isopropyl tri(dioctylphospho)titanate. That is, the coupling agent may include one or a combination of two or more of γ-aminoethylaminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, polybutyl titanate, tetra-n-propyl titanate and isopropyl tri(dioctylphosphoyloxy) titanate.
[0032] According to a specific embodiment of the present invention, the mass fraction of the coupling agent in the raw material of the ultraviolet absorber chelate is generally 40 parts to 65 parts, and can be specifically 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, etc., and a range with any two of the above specific values as endpoints.
[0033] According to a specific embodiment of the present invention, the boiling point of the first solvent is above 100° C. The first solvent can reduce viscosity and improve reaction uniformity during the reaction of the ultraviolet absorber A, the ultraviolet absorber B and the light stabilizer.
[0034] In some specific embodiments, the first solvent may include one or a combination of two or more of propylene glycol methyl ether, butyl acetate, ethyl propionate, butanol (such as n-butanol), etc.
[0035] According to a specific embodiment of the present invention, the mass fraction of the first solvent in the raw material of the ultraviolet absorber chelate is generally 10 parts to 30 parts, and can be specifically 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc., and a range with any two of the above specific values as endpoints.
[0036] The present invention also provides a method for preparing the above-mentioned ultraviolet absorber chelate, which comprises:
[0037] The light stabilizer, the ultraviolet absorber A, the ultraviolet absorber B, the coupling agent and the first catalyst are mixed and subjected to a first reaction to obtain the ultraviolet absorber chelate.
[0038] In the preparation method of the ultraviolet absorber chelate, the light stabilizer and ultraviolet absorber A, ultraviolet absorber B, and coupling agent form a chelate through a first reaction, the absorption peak of the ultraviolet absorber chelate is offset relative to the absorption peaks of the two raw material ultraviolet absorbers, and the chelate has an absorption capacity for ultraviolet light with a wavelength of 380-400nm. At the same time, the generated chelate can also improve the weather resistance of the product. The ultraviolet absorber chelate is applied to the preparation of a coating liquid to obtain a coating liquid with good ultraviolet isolation performance.
[0039] In the preparation method of the ultraviolet absorber chelate, the temperature of the first reaction is 120-150°C, and can be 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, and other specific values, and ranges with any two of the above specific values as endpoints; the time of the first reaction is 2h-6h, and can be 2h, 3h, 4h, 5h, 6h, and other specific values, and ranges with any two of the above specific values as endpoints. In some specific embodiments, the first reaction can be a reflux reaction.
[0040] According to a specific embodiment of the present invention, the above-mentioned preparation method may specifically include: adding ultraviolet absorber A, ultraviolet absorber B, coupling agent, first solvent, light stabilizer and first catalyst to a reaction device (generally a device with a stirring oil bath pot and a reflux device), adjusting the heating power and constant temperature of the reaction device, and turning on the stirring and heating functions of the oil bath pot, stirring and refluxing at a constant temperature to react, and turning off the heating function after the reaction is completed; after cooling to room temperature, taking out the reaction product, which is the ultraviolet absorber chelate, and setting it aside.
[0041] The present invention also provides a coating liquid, wherein the total mass of the coating liquid is 100%, the raw materials of the coating liquid include:
[0042] 10%-30% alkoxysilane, 30%-60% second solvent, 10%-25% ultraviolet absorber chelate provided by the present invention, 0.01%-1% second catalyst, 0.5%-3% auxiliary agent, 10%-30% water, the sum of the mass of the above components is 100%.
[0043] According to a specific embodiment of the present invention, the alkoxysilane can generate silicon oxide by hydrolysis reaction under the catalytic action of the second catalyst. The alkoxysilane can include one or a combination of two or more of methyl orthosilicate, ethyl orthosilicate, trimethoxysilane, triethoxysilane and dimethyldimethoxysilane.
[0044] According to a specific embodiment of the present invention, the mass proportion of the alkoxysilane in the raw materials of the coating liquid is generally 10%-30%, and can be specifically 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25%, 27.5%, 30% and other specific values, as well as a range with any two of the above specific values as endpoints. According to a specific embodiment of the present invention, the molecules derived from the coupling agent in the ultraviolet absorber chelate can react with alkoxysilane, thereby improving the weather resistance and wear resistance of the coating formed by the coating liquid. The present invention has found that by controlling the mass ratio of the coupling agent (one of the raw materials of the ultraviolet absorber chelate) to the alkoxysilane, the weather resistance and wear resistance of the coating formed by the coating liquid can be adjusted; when the amount of coupling agent added increases, the weather resistance of the coating can be improved, but the wear resistance of the coating will be reduced. Specifically, when the mass ratio of the coupling agent to the alkoxysilane is less than 0.3:1, the radiation resistance of the coating formed by the coating liquid is less than 1000h; when the mass ratio of the coupling agent to the alkoxysilane is greater than 1.2:1, the haze difference of the coating formed by the coating liquid before and after the abrasion resistance test is greater than 5%; controlling the mass ratio of the coupling agent to the alkoxysilane to 0.3-1.2:1 can have both good weather resistance and wear resistance, and the radiation resistance of the coating formed by the coating liquid obtained is ≥100h, and the haze difference before and after the abrasion resistance test is ≤5%.
[0045] The ultraviolet absorber chelate contained in the above coating liquid has an absorption peak at 280-400nm, has a double absorption peak, and is made of at least two ultraviolet absorbers (ultraviolet absorber A and ultraviolet absorber B).
[0046] According to a specific embodiment of the present invention, the UV absorber A and UV absorber B as raw materials of the UV absorber chelate have two absorption peaks before the reaction; after the reaction, the obtained UV absorber chelate has not only the two absorption peaks of the two raw UV absorbers, but also a new absorption peak at 380-400nm, and the UV absorption capacity is significantly improved (see Figure 3 In some specific embodiments, the absorption peaks of the UV absorber chelate (two or more) are located at 280-400 nm.
[0047] According to a specific embodiment of the present invention, the mass proportion of the ultraviolet absorber chelate in the raw materials of the coating liquid is generally 10%-25%, and can be specifically 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0048] According to a specific embodiment of the present invention, the second solvent may include one or a combination of two or more of ethanol, isopropanol, butanol (such as n-butanol) and propylene glycol methyl ether.
[0049] According to a specific embodiment of the present invention, the mass proportion of the second solvent in the raw material of the coating liquid is generally 30%-60%, and can be 30%, 35%, 40%, 45%, 50%, 55%, 60% and other specific values, and a range with any two of the above specific values as endpoints. According to a specific embodiment of the present invention, the second catalyst includes an inorganic acid that can catalyze the hydrolysis and polycondensation of alkoxysilane. Specifically, the second catalyst includes one or a combination of two or more of hydrochloric acid, nitric acid, sulfuric acid, and acetic acid.
[0050] According to a specific embodiment of the present invention, the mass proportion of the second catalyst in the raw materials of the coating liquid is generally 0.01%-1%, and specifically can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0051] According to a specific embodiment of the present invention, the mass proportion of the auxiliary agent in the raw materials of the coating liquid is generally 0.5%-3%, and can be specifically 0.5%, 1%, 1.5%, 2%, 2.5%, 3% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0052] According to a specific embodiment of the present invention, the auxiliary agent includes one or a combination of two or more of a leveling agent, a defoaming agent, and a wetting agent.
[0053] Among the above-mentioned additives, the leveling agent may include one or a combination of two or more of BYK-332, BYK-333, BYK-341 and BYK-348.
[0054] In the above-mentioned auxiliary agents, the defoaming agent includes one or a combination of two or more of BYK-020, BYK-022, BYK-028 and BYK-080A.
[0055] In the above-mentioned additives, the lubricant includes one or a combination of two or more of BYK-110, BYK-170, BYK-171 and BYK-180.
[0056] According to a specific embodiment of the present invention, the mass proportion of water in the raw materials of the coating liquid is generally 10%-30%, and can be specifically 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25%, 27.5%, 30% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0057] The present invention also provides a method for preparing the coating liquid, which comprises: mixing the ultraviolet absorber chelate with alkoxysilane, a second solvent, a second catalyst, an auxiliary agent and water, and performing a second reaction to obtain the coating liquid.
[0058] In the method for preparing the coating liquid, the second reaction is a hydrolysis reaction of alkoxysilane catalyzed by a second catalyst to generate silicon oxide. The temperature of the second reaction is 20°C-50°C, and can be specifically 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, and other specific values, as well as a range with any two of the above specific values as endpoints; the time of the second reaction is 30min-120min, and can be specifically 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, and other specific values, as well as a range with any two of the above specific values as endpoints.
[0059] According to a specific embodiment of the present invention, the reaction product obtained through the second reaction is silica sol, and the water in the above-mentioned coating can ensure that the silica sol evaporates at a suitable speed to form a uniform coating.
[0060] According to a specific embodiment of the present invention, the preparation method of the above coating may specifically include:
[0061] The weighed second solvent, alkoxysilane, ultraviolet absorber chelate, second catalyst, water and auxiliary agent are added to a conical flask in sequence, stirred for a period of time (30min-120min) at a certain temperature (20°C-50°C) to carry out a second reaction, and then the stirred product is taken out and filtered (a filter with a certain mesh size can be used) to obtain a coating; the coating can be placed in a light-shielding sealed container (such as a light-shielding sealed plastic bottle) for standby use.
[0062] The present invention also provides a coating, which is formed by drying and curing the above-mentioned coating liquid. The coating contains silicon dioxide and ultraviolet absorber chelate, and the transmittance of UVB (wavelength 280-315nm) and UVA (wavelength 315-400nm) light is less than or equal to 2%, and can further reach less than or equal to 1%, and has a high ultraviolet blocking ability. In some specific embodiments, the curing temperature can be 80°C-200°C, specifically 80°C, 90°C, 100°C, 150°C, 200°C and other specific values, as well as a range with any two of the above specific values as endpoints; the curing time is 10min-200min, specifically 10min, 50min, 100min, 150min, 200min and other specific values, as well as a range with any two of the above specific values as endpoints.
[0063] The present invention also provides a coated glass, which comprises a glass substrate and a coating, wherein the coating is arranged on at least one surface of the glass substrate; the coating is formed by drying and curing the coating liquid provided by the present invention.
[0064] In the above-mentioned coated glass, the thickness of the coating is generally controlled to be 5μm-10μm, specifically 5μm, 6μm, 7μm, 8μm, 9μm, 10μm and other specific values, and a range with any two of the above specific values as endpoints, and can be further controlled to be 6μm-8μm.
[0065] In the above-mentioned coated glass, the glass substrate may be curved glass, and the original sheet of the glass substrate may include one of float glasses such as float white glass, float grey glass, and float dark white glass.
[0066] According to a specific embodiment of the present invention, the transmittance of the coated glass for light with an incident angle of 0°-90° and a wavelength of 280-315nm is less than or equal to 2%, and further less than or equal to 1%; the transmittance of the coated glass for light with an incident angle of 0°-90° and a wavelength of 315-400nm is less than or equal to 2%, and further less than or equal to 1%. The above transmittance can be calculated based on the spectrophotometer scanning results of the coated glass, and the calculation method can be based on any one of the automotive glass optical test standards such as ISO9050, ISO13837, average transmittance, and any single point transmittance.
[0067] The coating formed by the coating liquid provided by the present invention can effectively block ultraviolet light. The coated glass containing the coating has a high ultraviolet blocking ability and can be used as a high ultraviolet insulating coated glass.
[0068] According to a specific embodiment of the present invention, the UV blocking capability of the coated glass is increased relative to that of the glass substrate without the coating, while the visible light transmittance is not significantly reduced. In some specific embodiments, the coated glass has a T400nm (400nm single point transmittance) of ≤1%, and the difference between the visible light transmittance of the coated glass and the visible light transmittance of the glass substrate without the coating is less than or equal to 5%.
[0069] According to a specific embodiment of the present invention, the coating layer in the coated glass has high adhesion to the glass substrate; the coated glass is used as automobile glass to ensure driving safety. In some specific embodiments, the coated glass can reach level 0 in a hundred-grid knife test.
[0070] According to a specific embodiment of the present invention, the coated glass has high wear resistance. For example, the haze difference of the coating before and after the wear test can be controlled within 5%, and the wear test can be specifically as follows: the coated glass is placed in a plane abrasion tester with the coating facing upward, the test pressure is 4.9N, and a plane abrasion test is performed for 1000 revolutions, and the haze meter is used to test the area of the sample that has not been subjected to the wear test to obtain the haze H1, and the area that has been subjected to the wear test is tested to obtain the haze H2, and the haze difference before and after the test = H2-H1.
[0071] According to a specific embodiment of the present invention, the coated glass has good weather resistance.
[0072] The present invention also provides a method for preparing the coated glass, which comprises: applying the coating to the surface of a glass substrate for leveling, and drying and curing the coating to obtain the glass.
[0073] In the method for preparing the coated glass, the curing temperature is 80° C.-200° C., and the curing time is 10 min-200 min.
[0074] In the method for preparing the coated glass, the leveling temperature may be 15° C.-30° C., the leveling humidity may be 45% RH-75% RH, and the leveling time may be 1 min-20 min.
[0075] In the above-mentioned method for preparing coated glass, the coating method may include one of spin coating, roller coating, dip coating, flow coating, shower coating or spray coating.
[0076] The beneficial effects of the present invention include:
[0077] The coating formed by the coating provided by the present invention has high ultraviolet light blocking performance, especially the transmittance of ultraviolet light of UVB and UVA can be as low as below 2%, thereby improving customer satisfaction of the product; at the same time, the high ultraviolet light blocking coating also has excellent wear resistance; and the VOC emission of the coating is extremely low, and it has the advantages of being green and environmentally friendly and having good construction performance; applying the coating to glass can improve the ultraviolet light blocking ability of the glass, and can comply with the regulations on automotive glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 Schematic diagrams of the structures of coated glasses of Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention.
[0079] Figure 2 This is the infrared characterization result of test example 1.
[0080] Figure 3 This is the absorbance test result of Test Example 1.
[0081] Description of Reference Numerals: glass substrate 100 , coating layer 101 . DETAILED DESCRIPTION
[0082] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0083] In the following experiments, UV absorber A is Chiguard 1033, UV absorber B is triazine UV absorber Chiguard 1064, light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and the first catalyst is dodecyltrimethylammonium chloride.
[0084] Preparation Example 1
[0085] This preparation example provides a UV absorber chelate, and the preparation method of the chelate is as follows:
[0086] Weigh 20 g of n-butanol, 5 g of ultraviolet absorber A, 10 g of ultraviolet absorber B, 0.3 g of light stabilizer, 65 g of γ-methacryloxypropyltrimethoxysilane, and 0.05 g of the first catalyst into a round-bottom flask, place the conical flask in an oil bath, start stirring and heating, design the temperature of the oil bath to be 120°C, reflux for 120 min, turn off the heating of the oil bath, stir while cooling naturally to room temperature, and obtain about 100 g of chelate A1.
[0087] Preparation Example 2
[0088] This preparation example provides a UV absorber chelate, and the preparation method of the chelate is as follows:
[0089] Weigh 30 g of n-butanol, 5 g of ultraviolet absorber A, 0.3 g of light stabilizer, 65 g of γ-methacryloxypropyltrimethoxysilane, and 0.05 g of the first catalyst into a round-bottom flask, place the conical flask in an oil bath, start stirring and heating, design the temperature of the oil bath to be 120°C, reflux for 120 min, turn off the heating of the oil bath, stir while cooling naturally to room temperature, and obtain about 100 g of chelate A2.
[0090] Preparation Example 3
[0091] This preparation example provides a UV absorber chelate, and the preparation method of the chelate is as follows:
[0092] Weigh 25 g of n-butanol, 10 g of ultraviolet absorber B, 0.3 g of light stabilizer, 65 g of γ-methacryloxypropyltrimethoxysilane, and 0.05 g of the first catalyst into a round-bottom flask, place the conical flask in an oil bath, start stirring and heating, design the temperature of the oil bath to be 120°C, reflux for 120 min, turn off the heating of the oil bath, stir while cooling naturally to room temperature, and obtain about 100 g of chelate A3.
[0093] Preparation Example 4
[0094] This preparation example provides a UV absorber chelate, and the preparation method of the chelate is as follows:
[0095] Weigh 20 g of n-butanol, 5 g of ultraviolet absorber A, 10 g of ultraviolet absorber B, 65 g of γ-methacryloxypropyltrimethoxysilane, and 0.05 g of the first catalyst into a round-bottom flask, place the conical flask in an oil bath, start stirring and heating, design the temperature of the oil bath to be 120°C, reflux for 120 min, turn off the heating of the oil bath, stir while cooling naturally to room temperature, and obtain about 100 g of chelate A4.
[0096] Preparation Example 5
[0097] This preparation example provides a UV absorber chelate, and the preparation method of the chelate is as follows:
[0098] Weigh 20 g of n-butanol, 5 g of ultraviolet absorber A, 10 g of ultraviolet absorber B, 0.3 g of light stabilizer, 131.9 g of γ-methacryloxypropyltrimethoxysilane, and 0.05 g of the first catalyst into a round-bottom flask, place the conical flask in an oil bath, start stirring and heating, design the temperature of the oil bath to be 120°C, reflux for 120 min, turn off the heating of the oil bath, stir while cooling naturally to room temperature, and obtain about 167 g of chelate A5.
[0099] Example 1
[0100] This embodiment provides a coating, and the preparation method thereof includes:
[0101] Weigh 54 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 15 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B1.
[0102] This embodiment also provides a coated glass, such as Figure 1As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing a coating B1. In this embodiment, the glass substrate 100 is a curved glass.
[0103] The preparation method of the above-mentioned coated glass is as follows:
[0104] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B1 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high ultraviolet isolation coating with a thickness of 5 μm-6 μm. The curved glass substrate with the coating was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C1, which can be used as high ultraviolet isolation coated automotive glass.
[0105] Example 2
[0106] This embodiment provides a coating liquid, and the preparation method of the coating liquid includes:
[0107] Weigh 49 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 20 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B2.
[0108] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100. The coating 101 is formed by curing a coating B2. In this embodiment, the glass substrate 100 is a curved glass.
[0109] The preparation method of the above-mentioned coated glass is as follows:
[0110] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B2 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C2, which can be used as high UV isolation coated automotive glass.
[0111] Example 3
[0112] This embodiment provides a coating liquid, and the preparation method of the coating liquid includes:
[0113] Weigh 44 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 25 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B3.
[0114] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing the coating B3. In this embodiment, the glass substrate 100 is a curved glass.
[0115] The preparation method of the above-mentioned coated glass is as follows:
[0116] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B3 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high ultraviolet isolation coating with a thickness of 5 μm-6 μm. The curved glass substrate with the high ultraviolet isolation coating was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C3, which can be used as high ultraviolet isolation coating automotive glass.
[0117] Example 4
[0118] This embodiment provides a coating, and the preparation method thereof includes:
[0119] Weigh 48 g of propylene glycol methyl ether, 12 g of ethyl orthosilicate, 24 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B4.
[0120] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100. The coating 101 is formed by curing the coating B4. In this embodiment, the glass substrate 100 is a curved glass.
[0121] The preparation method of the above-mentioned coated glass is as follows:
[0122] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B4 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C4, which can be used as high UV isolation coated automotive glass.
[0123] Example 5
[0124] This embodiment provides a coating, and the preparation method thereof includes:
[0125] Weigh 40 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 15 g of chelate A1, 0.02 g of acetic acid, 30 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B5.
[0126] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing the coating B5. In this embodiment, the glass substrate 100 is a curved glass.
[0127] The preparation method of the above-mentioned coated glass is as follows:
[0128] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B5 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C5, which can be used as high UV isolation coated automotive glass.
[0129] Example 6
[0130] This embodiment provides a coating, and the preparation method thereof includes:
[0131] Weigh 40 g of propylene glycol methyl ether, 29 g of ethyl orthosilicate, 14.5 g of chelate A1, 0.9 g of acetic acid, 15 g of deionized water, 0.4 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B6.
[0132] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing the coating B6. In this embodiment, the glass substrate 100 is a curved glass.
[0133] The preparation method of the above-mentioned coated glass is as follows:
[0134] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B6 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C6, which can be used as high UV isolation coated automotive glass.
[0135] Example 7
[0136] This embodiment provides a coating, and the preparation method thereof includes:
[0137] Weigh 50 g of propylene glycol methyl ether, 10 g of ethyl orthosilicate, 23 g of chelate A1, 0.02 g of nitric acid, 16 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B7.
[0138] This embodiment also provides a coated glass, such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing the coating B7. In this embodiment, the glass substrate 100 is a curved glass.
[0139] The preparation method of the above-mentioned coated glass is as follows:
[0140] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B7 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C7, which can be used as high UV isolation coated automotive glass.
[0141] Comparative Example 1
[0142] This comparative example provides a coating liquid, and the preparation method of the coating liquid comprises:
[0143] Weigh 60 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 9 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B8.
[0144] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100. The coating 101 is formed by curing the coating B8. In this embodiment, the glass substrate 100 is a curved glass.
[0145] The preparation method of the above-mentioned coated glass is as follows:
[0146] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B8 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high-ultraviolet isolation coating with a thickness of 5 μm-6 μm. The curved glass substrate with the high-ultraviolet isolation coating was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C8, which can be used as high-ultraviolet isolation coated automotive glass.
[0147] Comparative Example 2
[0148] This comparative example provides a coating liquid, and the preparation method of the coating liquid comprises:
[0149] Weigh 40 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 30 g of chelate A1, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B9.
[0150] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100. The coating 101 is formed by curing the coating B9. In this embodiment, the glass substrate 100 is a curved glass.
[0151] The preparation method of the above-mentioned coated glass is as follows:
[0152] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B9 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high-ultraviolet isolation coating with a thickness of 5 μm-6 μm. The curved glass substrate with the high-ultraviolet isolation coating was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C9, which can be used as high-ultraviolet isolation coated automotive glass.
[0153] Comparative Example 3
[0154] This comparative example provides a coating liquid, and the preparation method of the coating liquid comprises:
[0155] Weigh 54 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 15 g of chelate A2, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B10.
[0156] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing a coating B10. In this embodiment, the glass substrate 100 is a curved glass.
[0157] The preparation method of the above-mentioned coated glass is as follows:
[0158] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B10 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C10, which can be used as high UV isolation coated automotive glass.
[0159] Comparative Example 4
[0160] This comparative example provides a coating liquid, and the preparation method of the coating liquid comprises:
[0161] Weigh 54 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 15 g of chelate A3, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B11.
[0162] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing a coating B11. In this embodiment, the glass substrate 100 is a curved glass.
[0163] The preparation method of the above-mentioned coated glass is as follows:
[0164] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B11 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C11, which can be used as high UV isolation coated automotive glass.
[0165] Comparative Example 5
[0166] This comparative example provides a coating liquid, and the preparation method of the coating liquid comprises:
[0167] Weigh 54 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 15 g of chelate A4, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B12.
[0168] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing a coating B12. In this embodiment, the glass substrate 100 is a curved glass.
[0169] The preparation method of the above-mentioned coated glass is as follows:
[0170] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B12 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C12, which can be used as high UV isolation coated automotive glass.
[0171] Comparative Example 6
[0172] This comparative example provides a coating, and its preparation method comprises:
[0173] Weigh 54 g of propylene glycol methyl ether, 15 g of tetraethyl orthosilicate, 3 g of butanol, 0.75 g of ultraviolet absorber A, 1.5 g of ultraviolet absorber B, 0.05 g of light stabilizer, 9.7 g of γ-methacryloxypropyltrimethoxysilane, 0.0075 g of the first catalyst, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40°C water bath for 60 min to obtain coating B13.
[0174] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100. The coating 101 is formed by curing a coating B13. In this embodiment, the glass substrate 100 is a curved glass.
[0175] The preparation method of the above-mentioned coated glass is as follows:
[0176] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B13 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C13, which can be used as high UV isolation coated automotive glass.
[0177] Comparative Example 7
[0178] This comparative example provides a coating, and its preparation method comprises:
[0179] Weigh 54 g of propylene glycol methyl ether, 15 g of ethyl orthosilicate, 25 g of chelate A5, 0.3 g of acetic acid, 15 g of deionized water, 0.5 g of BYK-333, and 0.2 g of BYK-180; stir the above ingredients in a 40° C. water bath for 60 min to obtain coating B14.
[0180] This comparative example also provides a coated glass such as Figure 1 As shown, the coated glass comprises a glass substrate 100 and a coating 101. The coating 101 is located on at least one surface of the glass substrate 100 and is formed by curing a coating B14. In this embodiment, the glass substrate 100 is a curved glass.
[0181] The preparation method of the above-mentioned coated glass is as follows:
[0182] In a 10,000-class clean room, at a temperature of 22°C ± 3°C and a humidity of 65% RH ± 5% RH, a manual spray gun was used to apply coating B14 on the surface of a cleaned curved glass substrate and the coating was allowed to stand for 10 minutes. After the coating liquid on the surface of the curved glass substrate was leveled, an infrared lamp was used to pre-dry the coating liquid to form a high UV isolation coating with a thickness of 5 μm-6 μm. The coated curved glass substrate was then placed at 120°C for curing for 60 minutes. The curved glass substrate was taken out after naturally cooling to room temperature to obtain coated glass C14, which can be used as high UV isolation coated automotive glass.
[0183] The test methods used in the following test cases are:
[0184] Visible light transmittance: A spectrophotometer (instrument model: Perkin Elmer, Lambda 950) was used to measure the transmittance spectrum in the wavelength range of 250nm-2550nm, and the test angles were 5°, 45°, and 90° respectively.
[0185] The visible light transmittance is calculated according to ISO9050 standard; the optical transmittance in this test is the average value obtained by measuring five different points on the same sample.
[0186] UV transmittance: The UV part 280nm-400nm takes a value every 10nm, and the average value is obtained by measuring the UV transmittance of five different points on the same sample.
[0187] Coating thickness: The step profiler (instrument model: KLA-TENCOR P16+ USA) measures the coating thickness.
[0188] Wear resistance: Use a flat abrasion tester (instrument model: Taber 5135, USA). Cut a 10 cm × 10 cm sample and place the sample on the instrument with the coating facing upwards. Perform flat abrasion for 1000 turns with a pressure of 4.9N.
[0189] Haze test: Place the abrasion test sample in the haze meter (instrument model: HZ-V3 Japan). The unpolished area is tested to get the haze Haze1. Move the sample and test the polished area to get the haze Haze2. The haze difference before and after = |Haze2-Haze1|.
[0190] Coating weather resistance test: The weather resistance test refers to GB / T31849-2015 "Automobile Film Glass", cut a 10cm×30cm sample, and face the coating surface of the sample to the light source (wavelength range 300-400nm), irradiate continuously for 100h, and use a spectrophotometer to test Tuv (ultraviolet transmittance) (Tuv is calculated according to ISO13837), and the difference before and after the experiment is recorded as ΔTuv.
[0191] Coating adhesion test: Adhesion test refers to ISO 2409 standard, and Table 1 lists the grade assessment standard of adhesion. Use the 5123 grid knife produced by BYK Company of Germany. First, fix the coated glass surface upward on the experimental platform, select 1 1mm blade × 1 (11 blades), control the pressure when the blade scratches the glass, let the grid knife scratch about 10cm on the coating surface, and then scratch the grid knife at an angle perpendicular to the first scratch to form 100 square grids. Cut about 10cm of the specified tape, press the tape on the scratched grid, ensure that the tape completely covers the grid, and then quickly pull up the tape within 0.5-1s, and the angle of the tape pulling up is 60° with the coating surface; finally, use a brush to brush the impurities remaining in the cutting area, use a magnifying glass to observe the 100 square grids cut by the grid knife, and refer to the evaluation table 1 to judge the adhesion grade of the coating.
[0192] Table 1 Adhesion grade evaluation
[0193]
[0194]
[0195] Test Example 1
[0196] The structure of the chelate prepared in the example was characterized.
[0197] The unreacted raw material in Preparation Example 1 was subjected to infrared characterization and absorbance test, and the results were as follows: Figure 2 , Figure 3 The curve before chelation is shown in FIG. 1 ; the chelate obtained after the reaction is then characterized as above, and the results are as follows Figure 2 , Figure 3 As shown in the curve of "after chelation".
[0198] from Figure 2 It can be seen that compared with the raw material before the reaction, the sample after the reaction has a -1 A new peak is generated at 3500cm, indicating that aromatic ether ketone ether with oxygen connected to the side chain carbon may appear after the reaction. -1The peak at is more obvious, indicating that there may be more free hydroxyl groups here. The above may be the reason why a new absorption peak appears near 360nm of ultraviolet light after the reaction.
[0199] from Figure 3 It can be seen that the raw materials before the reaction have two absorption peaks in the 280-350nm band, and these absorption peaks come from the two raw material ultraviolet absorbers; the chelate after the reaction not only retains the two absorption peaks before the reaction, but also produces a new absorption peak at the position of 360-400nm. This result shows that the present invention produces a new functional group in the chelate obtained by performing the first reaction, and adds the absorption capacity of light with a wavelength of 380-400nm, and the ultraviolet absorption capacity is significantly enhanced.
[0200] Test Example 2
[0201] This test example provides the performance test results of the coated glasses of the above embodiments and comparative examples.
[0202] The evaluation results of the visible light transmittance, ultraviolet transmittance, film thickness, coating wear resistance, coating weather resistance, and adhesion between coating and glass of the coated glass of each embodiment are shown in Table 2 and Table 3. In addition, a glass substrate (uncoated blank glass) is provided as a control sample of the above-mentioned coated glass. The "visible light transmittance change value" in Table 2 and Table 3 is the difference in visible light transmittance between the coated glass of the embodiment and the uncoated blank glass. Table 4 and Table 5 are the evaluation results of the visible light transmittance, ultraviolet transmittance, film thickness, coating wear resistance, coating weather resistance, and adhesion between coating and glass of the coated glass of each comparative example.
[0203] Table 2 Evaluation results of blank glass and coated glass of Examples 1-3
[0204]
[0205] Table 3 Evaluation results of coated glasses of Examples 4-7
[0206]
[0207]
[0208] Table 4 Evaluation results of coated glass of comparative examples 1-4
[0209]
[0210]
[0211] Table 5 Evaluation results of coated glass of comparative examples 5-7
[0212]
[0213]
[0214] It can be seen from Table 2 and Table 3 that the coated glass provided in the embodiment has excellent visible light transmittance, high ultraviolet light isolation performance, wear resistance, and coating adhesion. Specifically, the difference in visible light transmittance between the coated glass and the blank glass plate without coating is less than or equal to 5%; the transmittance of the coated glass for ultraviolet light with an incident angle of 5-90° and a wavelength of 280-400nm (especially light with a wavelength of 380-400nm) is less than or equal to 1%; the change in visible light transmittance is less than 2%; the difference in haze before and after the wear test of the coated glass is less than or equal to 5%; the change in ultraviolet transmittance of the coating after radiation resistance is less than 1%, and the test result of the coated glass can reach level 0.
[0215] Comparing the test results in Table 2, Table 3 with Table 4, Table 5, we can see that:
[0216] In Comparative Example 1, when the amount of chelate added is too low, the weather resistance of the coating is reduced, the UV shielding ability is reduced, and the bonding strength between the coating and the glass is reduced; however, the visible light transmittance of the coating is improved, and the wear resistance is improved.
[0217] In Comparative Example 2, when the amount of the chelate added is too large, the visible light transmittance of the coating decreases and the wear resistance decreases; however, the weather resistance of the coating is improved, the UV shielding ability is improved, and the bonding strength between the coating and the glass is improved.
[0218] In Comparative Example 3, no ultraviolet absorber A was added to the raw materials of the ultraviolet absorber chelate. Although the visible light transmittance, weather resistance, adhesion between the coating and glass, and wear resistance of the coating prepared therefrom did not change much from those in Example 1, they could not meet the requirement of <1% in the ultraviolet 280nm-320nm region.
[0219] In Comparative Example 4, no ultraviolet absorber B was added to the raw materials of the ultraviolet absorber chelate, and the visible light transmittance, weather resistance, adhesion between the coating and glass, and wear resistance of the coating did not change much from those in Example 1; however, the requirement of <1% could not be met in the ultraviolet 320nm-400nm region.
[0220] In Comparative Example 5, no light stabilizer is added to the raw materials of the ultraviolet absorber chelate. Although the visible light transmittance, weather resistance, adhesion between the coating and glass, and wear resistance of the coating are not much different from those in Example 1, the requirement of <1% cannot be met in the ultraviolet 380nm-400nm region.
[0221] By comparing the test results of Comparative Examples 3 to 5 with those of Example 1, it can be seen that when the existing ultraviolet absorber is added alone, the resulting coating can only absorb ultraviolet light corresponding to the absorption band of the raw material ultraviolet absorber, while the ultraviolet absorber chelate generated by the reaction of two ultraviolet absorbers with a light stabilizer in the present invention not only retains the absorption capacity of the raw material ultraviolet absorber (280-380nm), but also expands the absorption range to 380-400nm, and maintains the light transmittance below 1% in the entire absorption range (280-400nm), and has a high ultraviolet isolation ability.
[0222] In Comparative Example 6, the chelate used to prepare the coating was not subjected to the first reaction, and the coating was cracked in the weather resistance test, indicating that the weather resistance of the coating was significantly reduced; in addition, the wear resistance of the coating in Comparative Example 6 was also reduced.
[0223] In Comparative Example 7, the coupling agent in the chelate compound is excessive, resulting in a significant decrease in the wear resistance of the coating and a decrease in weather resistance.
[0224] It can be seen from the above test results that the coating provided by the present invention can be cured to form a coating with high visible light transmittance, high UV isolation performance, high wear resistance and high adhesion. Glass containing the coating can be used as automotive glass with high UV isolation coating.
Claims
1. A UV absorber chelate, wherein: The raw materials of the ultraviolet absorber chelate include, by weight: First solvent: 10 parts to 30 parts, UV absorber A: 2.5 parts to 10 parts, UV absorber B: 2.5 parts to 15 parts, light stabilizer: 0.05 parts to 1.5 parts, coupling agent: 40 parts to 65 parts, first catalyst: 0.01 parts to 0.1 parts; The absorption peak of the ultraviolet absorber A is located at 280nm-315nm; the absorption peak of the ultraviolet absorber B is located at 315nm-380nm.
2. The ultraviolet absorber chelate according to claim 1, wherein The ultraviolet absorber A and the ultraviolet absorber B respectively include one or a combination of two or more of the following agents: benzophenone ultraviolet absorbers, benzimidazole ultraviolet absorbers, triazine ultraviolet absorbers, oxalylanilide ultraviolet absorbers, Chiguard P, Chiguard 1033, and Chiguard 5540.
3. The ultraviolet absorber chelate according to claim 2, wherein The benzimidazole ultraviolet absorber includes one or a combination of two or more of 2-(2'-hydroxy-5'-methylphenyl)-benzotriazole, 2-(2'-hydroxy-3',5'-di[1,1-dimethylphenyl]phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'methylphenyl)-5-chloro-benzotriazole, Chiguard 234, and Chiguard 380; And / or, the benzophenone ultraviolet absorber includes 2-hydroxy-4-methoxybenzophenone and / or 2-hydroxy-4-octyloxybenzophenone; And / or, the triazine ultraviolet absorber includes one or a combination of two or more of 2-cyano-3,3-diphenylacrylate, 2-cyano-3,3-diphenylacrylate, Chiguard 1064, and Chiguard 5431; And / or, the oxalic acid anilide ultraviolet absorber includes N-(4-ethyl benzoate)-N',N'-(methyl, phenyl) formamidine and / or N,N'-bis(4-ethoxycarbonylphenyl)-N'-benzyl formamidine.
4. The ultraviolet absorber chelate according to claim 1, wherein The absorption peak of the ultraviolet absorber A is 290-305nm; And / or, the absorption peak of the ultraviolet absorber B is 340nm-380nm.
5. The ultraviolet absorber chelate compound according to claim 1, wherein The light stabilizer includes pentamethyl piperidinol, tetramethyl piperidinol, a polymer of succinic acid and (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol), polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol) ester, bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate, HS-3310, One or a combination of two or more of HS-508.
6. The ultraviolet absorber chelate compound according to claim 1, wherein The first catalyst includes one or a combination of two or more of benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.
7. The ultraviolet absorber chelate compound according to claim 1, wherein The coupling agent includes a silane coupling agent and / or a titanate coupling agent.
8. The ultraviolet absorber chelate compound according to claim 1 or 7, wherein The coupling agent includes one or a combination of two or more of γ-aminoethylaminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(2-aminoethyl)-aminopropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, polybutyl titanate, tetra-n-propyl titanate and isopropyl tri(dioctylphosphoyloxy) titanate.
9. A method for preparing the ultraviolet absorber chelate according to any one of claims 1 to 8, comprising: Mixing a light stabilizer, an ultraviolet absorber A, an ultraviolet absorber B, a coupling agent and a first catalyst, and performing a first reaction to obtain the ultraviolet absorber chelate; The temperature of the first reaction is 120-150° C., and the time of the first reaction is 2 h-6 h.
10. A coating liquid, wherein the raw materials of the coating liquid, based on the total mass of the coating liquid as 100%, include: 10%-30% of alkoxysilane, 30%-60% of a second solvent, 10%-25% of the ultraviolet absorber chelate according to any one of claims 1 to 8, 0.01%-1% of a second catalyst, 0.5%-3% of an auxiliary agent, and 10%-30% of water.
11. The coating liquid according to claim 10, wherein The alkoxysilane includes one or a combination of two or more of methyl orthosilicate, ethyl orthosilicate, trimethoxysilane, triethoxysilane and dimethyldimethoxysilane; And / or, the auxiliary agent includes one or a combination of two or more of a leveling agent, a defoaming agent, and a wetting agent.
12. A method for preparing the coating liquid according to any one of claims 10 to 11, comprising: The ultraviolet absorber chelate is mixed with alkoxysilane, a second solvent, a second catalyst, an auxiliary agent and water to carry out a second reaction to obtain the coating liquid.
13. The preparation method according to claim 12, wherein: The temperature of the second reaction is 20°C-50°C, and the time of the second reaction is 30min-120min.
14. A coating formed by drying and solidifying the coating solution according to claim 10 or 11.
15. A coated glass, comprising a glass substrate and a coating, wherein the coating is disposed on at least one surface of the glass substrate; The coating layer is formed by drying and solidifying the coating solution according to any one of claims 10 or 11.
16. The coated glass according to claim 15, wherein: The coating has a thickness of 5 μm-10 μm.
17. The coated glass according to claim 15, wherein the transmittance of the coated glass for light with an incident angle of 0°-90° and a wavelength of 280-315 nm is less than or equal to 2%; the transmittance of the coated glass for light with an incident angle of 0°-90° and a wavelength of 315-400 nm is less than or equal to 2%; And / or, T400nm of the coating glass is ≤1%.
18. A method for preparing the coated glass according to any one of claims 15 to 17, comprising: The coating is applied to the surface of the glass substrate for leveling, and the coating is dried and cured to obtain the glass.
19. The preparation method according to claim 18, wherein: The curing temperature is 80° C.-200° C., and the curing time is 10 min-200 min.
Citation Information
Patent Citations
Coating liquid for forming ultraviolet absorbing coatings and ultraviolet absorbing glass
CN103613280A
Anti-ultraviolet high-strength laminated glass
CN219446360U
Cited By
Ultraviolet absorber chelate, coating, and coated glass
WO2026092482A1